Copy letter from INAAVD to Patrick Keough regarding the reinstatement of Mr. Roche - Irish National Aid and Volunteers' Dependants' Fund; Keough, Patrick (1916)
Letter addressed to "13 Batchelor's Walk, / Dublin.".
On reverse, inscribed on headed paper "Irish National Aid Association / _ / Offices-Grand Central Halls, / 10 Exchequer Street, Dublin.".
Keywords: Employment; Ireland -- History -- 1910-1921; Ireland -- History -- Easter Rising, 1916